Fieldwork and Geodata Acquisition – Experiences with Students in the High Tatra - Sulzer Wolfgang; Gspurning Josef (Ekológia (Bratislava))
This paper is intended to show in an exemplary form the experiences, possibilities, difficulties, and results of Geospatial Technologies geodata acquisition in the alpine environment of High Tatra. This combined GIS, remote sensing, and cartography practice for geography students has been held almost every 2 years since 2002 on the south side of the High Tatra. The course imparts knowledge and skills about advanced methods and techniques of GIS- and remote sensing-based fieldwork. Taking into account the most important contents and competences of the study branches as stated in the local curricula, particular attention is paid to the following focal points: introduction to human- and physio-geographic settings in the investigation site, design and implementation of project-related geodatabases for the study area, GPS or device-supported sampling and integration of the results into a heterogeneous data environment of analog and digital geodata, metadata generation, and data quality issues. Selected natural, cultural/touristic, and ecological landscape topics had to be investigated by small student groups in each fieldwork year. From the beginning of planning and work assignment of a virtual project, the students had to work out time schedules and proposals and realize the project. During these about 20 years various thematic topics could be applied during this practice. Geodata acquisition at the home university (maps, satellite images, accompanying information as photographs, literature, etc.) must be planned and put into practice in the fields. During fieldwork, they have to map additional valuable information and (field)check and update their prepared database. Methods of acquiring (remote sensing) geodata as part of an applied project: primary acquisition methods, secondary acquisition methods, spatial data infrastructure, quality of geodata, metadata generation, and geodata management. After fieldwork, the students have to integrate the fieldwork data into their project analyses. Some results and problems of work are shown in this paper.